Being Chinese, becoming Chinese American - Chen, Shehong, 1954-; University of Illinois (Urbana-Champaign campus). Press ([Champaign] : University of Illinois Press, 2002)
"In this foundational study, Shehong Chen investigates how Chinese immigrants to the United States transformed themselves into Chinese Americans during the crucial period between 1911 and 1927"--Jacket.
A search for a modern China and challenges to traditional Chinese identity, 1911 -- Defending Chinese republicanism and debating Chineseness in the United States, 1912-14 -- Constructing a Chinese American identity, 1915 -- An ideological foundation of the Chinese American identity, 1916-24 -- Building permanent Chinese American communities and displaying American Chinatown culture, 1920-27 -- Appendix: political events in China, 1898-1924.
Includes bibliographical references (pages 219-227).
Apr. 2, 2003 viewing.
JSTOR
Keywords: Chinese Americans -- Ethnic identity; Chinese Americans -- Cultural assimilation; Chinese Americans -- Social conditions -- 20th century; United States -- Relations -- China; China -- Relations -- United States; Transnationalism; Américains d'origine chinoise -- Identité ethnique; Américains d'origine chinoise -- Acculturation; Américains d'origine chinoise -- Conditions sociales -- 20e siècle.; Transnationalisme; SOCIAL SCIENCE / General; Chinese Americans -- Cultural assimilation; Chinese Americans -- Ethnic identity; Chinese Americans -- Social conditions; International relations; Transnationalism; China; United States; Soziale Situation; Ethnische Identität; Chinesen; USA; Chinesen; 1900-1999